Mosaic habitats at Woranso-Mille (Ethiopia) during the Pliocene and implications for Australopithecus paleoecology and taxonomic diversity. Issue 163 (February 2022) - Su, Denise F.; Haile-Selassie, Yohannes
Abstract: Many important Pliocene hominin specimens have been recovered from Woranso-Mille, a paleontological research area in the Afar region of Ethiopia, including the complete cranium of Australopithecus anamensis, a partial skeleton of Australopithecus afarensis, mandibular and maxillary elements representing a new species, Australopithecus deyiremeda, and a partial foot of an as-yet-unnamed species. Woranso-Mille is the only site, so far, to have reported the co-existence of more than one early hominin species between 3.8 and 3.3 Ma and the temporal overlap between A. anamensis and A. afarensis . Thus, the site has important implications for our understanding of the paleoecology and taxonomic diversity of early hominins and their ecological niche. This paper explores the paleohabitats of Woranso-Mille through its faunal community ecological structure and taxonomic composition using correspondence analysis and Forbes modified similarity index. The results suggest that Pliocene Woranso-Mille was a mosaic of different habitat types, with riparian woodland and floodplain grassland along rivers draining into a lake, along with less mesic habitats such as woodland, grassland, and shrubland. The apparent high level of vegetation heterogeneity may have promoted dietary specializations and niche differentiation among the different Australopithecus species at Woranso-Mille and allowed for their co-existence at the site.